Historical and Pedagogical Dimension of the Content of Professional Training of Future Programmers in the Second Half of the XX– Beginning of the XXI Century - Galyna Lebed (Pedagogical Discourse, 2017)
The article is devoted to a problem of reconstruction, comprehension and systematization historico – pedagogical process of professional education content development for future programmers, learning its features and patterns as a necessary development condition of pedagogical science.The article stipulates that the content development of the professional education of future programmers in the second half of the XX – beginning of the XXI century is closely intertwined with technological progress, which has set new demands before higher technical school concerning the quality of specialists education, their scientific orientation in terms of mastering the advanced knowledge and methods. The rapid development of computer technology has caused a significant increase in need for specialists in programming, optimization, optimal control, information systems and so on.Transition of technical universities in the 90’s to degree system and the consequent - a need to develop a new generation of educational programs for training specialists of all levels also led to a fundamental content renewal of the future programmers professional education.Due to development of cross-platform products, was analyzed the tendency of increasing demands for wide profile professionals. Thereby, professional standards in the field of software development must reflect the requirements for continuous training of software developers. Continuous changes in technology almost every few years require constant adjustment of educational plans and academic disciplines, studied in universities.Key words: professional training software, information society, information technology, computerized systems, software.